1999
DOI: 10.1007/s002170050436
|View full text |Cite
|
Sign up to set email alerts
|

Keeping qualities of white pan bread upon storage: effect of selected enzymes on bread firmness and elasticity

Abstract: Several different types of enzymes and their blends were added to dough with the object of improving the shelf-life of white, lidded-pan bread during storage. Bread firmness and elasticity were determined at 24, 48 and 72 h to determine the influence of the enzymes. Addition of bacterial a-amylase, specially to blends of enzymes also containing lipase and pentosanase, improved white, lidded-pan bread quality by increasing elasticity and lowering firmness of crumb, and enhanced the keeping quality over time by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
0
9
0
11
Order By: Relevance
“…Some results indicated that added xylanases (or hemicellulases or pentosanases) did not modify the crumb-firming rate, but decrease the initial firmness, probably by increasing loaf volume (Rouau, El-Hayek, & Moreau, 1994). Gil, Callejo, Rodríguez, and Ruiz (1999) reported that the addition of pentosanase had no detectable effect on the firmness and staling rate of bread. On the other hand, the others showed that the addition of xylanases decreased the staling rate of breads (Laurikainen et al, 1998;Martínez-Anaya et al, 1997).…”
Section: Effect Of Xynb On Bread Shelf-lifementioning
confidence: 97%
“…Some results indicated that added xylanases (or hemicellulases or pentosanases) did not modify the crumb-firming rate, but decrease the initial firmness, probably by increasing loaf volume (Rouau, El-Hayek, & Moreau, 1994). Gil, Callejo, Rodríguez, and Ruiz (1999) reported that the addition of pentosanase had no detectable effect on the firmness and staling rate of bread. On the other hand, the others showed that the addition of xylanases decreased the staling rate of breads (Laurikainen et al, 1998;Martínez-Anaya et al, 1997).…”
Section: Effect Of Xynb On Bread Shelf-lifementioning
confidence: 97%
“…Conversely, other studies [25,26] describe that the addition of hemicellulases does not modify the crumb firming rate, but decreases the initial crumb firmness, probably by increasing loaf volume. On the other hand, Gil et al [27] reported that the addition of pentosanase had no detectable effect on the firmness and staling rate of bread. The origin of the anti-staling action of xylanases or pentosanases is not clear and contradictory information has been published about the mechanism of the improving effect of these enzymes.…”
Section: Effect Of Enzyme Treatment On Bread Shelf Lifementioning
confidence: 97%
“…A Tabela 8 mostra os valores de firmeza dos pães nos dias 1, 4 e 7, mostrando que há concordância com a literatura (BONET et al, 2006;GIL et al, 1999;KATINA et al, 2006;SAHLSTRÖM;BRATHEN, 1997), onde se afirma que devido às transformações ocorridas nos ingredientes e, principalmente, à retrogradação do amido, ocorre redução na maciez do miolo dos pães e aumento na força de compressão com o decorrer da vida de prateleira. Observa-se que os valores de firmeza variaram de 955,94 a 2073,91 g durante o tempo de armazenamento dos pães de forma.…”
Section: Firmeza Durante O Armazenamentounclassified
“…Têm sido raramente empregadas em panificação, devido ao efeito prejudicial observado pela ação das lipases endógenas, que liberam ácidos graxos insaturados (PYLER, 1988;TAIT;GALLIARD, 1988). As lipases podem produzir mono e diglicerídeos provenientes da adição de lipídeos, melhorando o volume específico, maciez do miolo e, conseqüentemente, retardando o envelhecimento dos pães (GIL et al, 1999). Além disso, as enzimas lipases proporcionam aumento da elasticidade e fortalecimento da massa (GOESAERT et al, 2005 08-12 (1995); carboidratos totais, por diferença, e fibra bruta (em quadruplicata), pela metodologia proposta pelo Instituto Adolfo Lutz (1985).…”
Section: Introductionunclassified